2008
DOI: 10.1016/j.reseneeco.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the declining energy intensity of the U.S. economy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…Although Wing (2008) [41] only studies a single county, this work is of interest because it focuses on energy intensity in the U.S. at an aggregate level and the multiple factors behind it over the period from 1958 to 2000. Specific attention is devoted to technical change and industry composition.…”
Section: Economic Growth-energy Consumption Nexusmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Wing (2008) [41] only studies a single county, this work is of interest because it focuses on energy intensity in the U.S. at an aggregate level and the multiple factors behind it over the period from 1958 to 2000. Specific attention is devoted to technical change and industry composition.…”
Section: Economic Growth-energy Consumption Nexusmentioning
confidence: 99%
“…Specific attention is devoted to technical change and industry composition. Wing (2008) [41] finds that changes in industrial composition and disembodied technological progress are the main sources of the decline in the energy intensity. Input substitution due to changes in the relative prices of inputs has only transitory impact.…”
Section: Economic Growth-energy Consumption Nexusmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a very large literature has shown that not all GDP is the same in terms of energy intensity. The type of GDP makes a difference: Industrial sectors show a higher energy use per GDP, in contrast to commercial or tertiary activities (Sue Wing ; Belzer ). Thus, economic structure and trade‐balance across cities are found to be important in shaping urban energy‐material flows.…”
Section: Introductionmentioning
confidence: 99%
“…Improving energy efficiency was taken as an inevitable choice for the protection of national energy security and sustained economic growth in [4]. Early understanding of energy efficiency was to provide the same energy services by reducing energy inputs in [5].…”
Section: Introductionmentioning
confidence: 99%